DEEP LEARNING IMPLEMENTATION IN ELEMENTARY SCHOOLS: ENHANCING CRITICAL THINKING AND MEANINGFUL LEARNING THROUGH CONTEXTUAL PEDAGOGY - Parjuangan Panggabean; Dinarti; Ahmad Zuhdi; Hamka (RADJA PUBLIKA, 2025)
Elementary education in Indonesia remains predominantly characterized by rote learning and teacher-centered practices, which constrain students’ critical thinking and meaningful engagement. This participatory action research investigated the implementation of deep learning pedagogy in a rural elementary school (SD Negeri 019 Bonan Dolok, Mandailing Natal, Sept–Oct 2025), involving 50 teachers, 75 students (grades 3–5), and three university researchers through six collaborative cycles. Multiple qualitative instruments—observations, reflective journals, interviews, and artifact analyses—were employed to capture pedagogical and behavioral transformations. Findings indicate a progressive shift from transmissive to inquiry-oriented teaching. Teachers increasingly used open-ended questioning, extended wait time, and authentic local contexts. Students demonstrated higher participation, analytical reasoning, and collaboration, although progress varied across ability levels. Key challenges included limited instructional time, assessment misalignment, and teachers’ initial discomfort with shared authority. Collaborative reflection and peer learning communities emerged as pivotal for sustaining innovation. Deep learning proved attainable in resource-constrained environments when supported by reflective professional development and school leadership. Theoretically, this study extends deep learning and contextual teaching frameworks into underexplored elementary contexts, identifying reflective collaboration as a critical mechanism for pedagogical transformation. Practically, it proposes a scalable, context-sensitive model for implementing deep learning in rural schools through participatory teacher development, offering actionable guidance for educators and policymakers seeking to foster critical, creative, and collaborative learning.